Exposing The Criteria For Fake Hadith In The Science Of Mustolahul Hadith - Nasiri (STID Raudlatul Iman Sumenep, 2024)
Scholars differ on when the forgery of hadith began. People have falsified various hadiths for varying motives and purposes. Furthermore, for certain interests, people are able and willing to fabricate them. The term